Repeated High Intensity Bouts with Long Recovery: Are Bicarbonate or Carbohydrate Supplements an Option?. (10th November 2014) - Stöggl, Thomas; Torres-Peralta, Rafael; Cetin, Ebru; Nagasaki, Masaru
Abstract : The effects of varying recovery modes and the influence of preexercise sodium bicarbonate and carbohydrate ingestion on repeated high intensity performance, acid-base response, and recovery were analyzed in 12 well-trained males. They completed three repeated high intensity running bouts to exhaustion with intervening recovery periods of 25 min under the following conditions: sodium bicarbonate, active recovery (BIC); carbohydrate ingestion, active recovery (CHO); placebo ingestion, active recovery (ACTIVE); placebo ingestion, passive recovery (PASSIVE). Blood lactate (BLa), blood gases, heart rate, and time to exhaustion were collected. The three high intensity bouts had a duration of 138 ± 9,   124 ± 6, and 121 ± 6  s demonstrating a decrease from bout 1 to bout 3. Supplementation strategy had no effect on performance in the first bout, even with differences in pH and bicarbonate (HCO 3 - ). Repeated sprint performance was not affected by supplementation strategy when compared to ACTIVE, while PASSIVE resulted in a more pronounced decrease in performance compared with all other interventions. BIC led to greater BLa, pH, and HCO 3 - values compared with all other interventions, while for PASSIVE the opposite was found. BLa recovery was lowest in PASSIVE; recovery in pH, and HCO 3 - was lower in PASSIVE and higher in BIC.